Accusing and Identifying the Kalku: The Perception of Sorcery in Mapuche Society (Seventeenth to Eighteenth Centuries). - Ambrogio, Oriol (Ethnohistory, 2021)
This article examines accusations of sorcery as a way to understand the perceptions of sorcery among the Mapuche of central-southern Chile during the colonial period. Local communities believed that illnesses and unfortunate events were caused by the actions of sorcerers, known as kalku, and therefore consulted ritual healers and diviners, the machi and dugul, to identify and punish the supposed evildoers. In accusing local members of being kalku, the ritual specialists expressed a precise perception of sorcery and developed clear strategies for counteracting the sorcerers. This article argues that the accusations of sorcery became political and social instruments in the hands of the local authorities and that they shaped the meaning of sorcery and its perception among the Mapuche.